Modulating Effect of Paeonol on Piglets With Ulcerative Colitis - Wang, Shanshan; Bai, Miaomiao; Shu, Qingyan; Liu, Zhengan; Shao, Yirui; Xu, Kang; Xiong, Xia; Liu, Hongnan; Li, Yao (Frontiers in Nutrition, 2022)
Piglet enteritis is a major problem that needs to be solved urgently in modern pig production. Paeonol (Pae) has been used as a novel treatment option due to its good medicinal value. This study purported to elucidate the regulatory mechanism of Pae on DSS-induced ulcerative colitis (UC) in weaned piglets. Thirty-six crossbred (Duroc × Landrace × Yorkshire) weaned piglets were stochastically split into 6 groups: the control group, DSS group, 0.2% Pae group, 0.4% Pae group, 0.8% Pae group and mesalazine group. The control group and DSS group were fed with basic diet, the Pae groups and mesalazine group were fed with 0.2%, 0.4%, 0.8% and 2g mesalazine per kilogram of basic diet in the whole experience. On the 15th day of the test period, the control group was gavaged with 10ml normal saline, while the remaining five groups were gavaged with 10ml 5% DSS solution for 13 days. The experiment lasted for 27 days. The results showed that the 0.8% Pae group significantly added the average daily feed intake (ADFI) and the Occludin mRNA expression in the colon of piglets (P<0.05). The 0.2% Pae group markedly added the average daily gain (ADG) and the expression of zonula occludens-1 (ZO-1) mRNA (P<0.05). The 0.2% and 0.4% Pae groups significantly reduced the feed to gain ratio (F/G) and the mRNA expression levels of Caspase8, respectively markedly enhanced the mRNA expression levels of transforming growth factor-β (TGF-β) and interleukins-4 (IL-4) (P<0.05). The relative abundance of Campilobacterota in the 0.8% Pae group was significantly reduced (P<0.05). The relative abundance of Firmicutes was observably increased in the 0.4% Pae group (P<0.05). In the 0.2% and 0.8% Pae groups, the relative abundance of Prevotella was markedly increased (P<0.05). The contents of propionic acid, butyric acid and valerate acid in 0.2% Pae group were markedly elevated (P<0.05). Thus, it is speculated that Pae may regulate the balance of anti-inflammatory/pro-inflammatory factors, improve intestinal tight junction expression, reduce apoptosis, improve intestinal microflora structure and growth performance of piglets, thereby restoring intestinal barrier function and alleviating DSS-induced UC in piglets.